Program Pemetaan Infrastruktur sebagai Upaya Mendukung Sistem Informasi Kelurahan Sisir, Kota Batu - Wibowo, Alvia Nayla; Putra, Adam Yosandhi; Khoir, Ahmad Husaini; Azziban, Achmad Muzaqi; Nisa, Ananda Zahratun; Istiqomah, Annisa Widhi; Anantara, Atha Azaria; Rohim, Bintang Fajar Ainur; Rakhman Putri, Clarintha Naylah; Pratama, Immanuel Surya; Annailah, Luthfiya; Aprilia, Safrina; Prayogo, Sahrul Faiz Dian; Rahayaan, Surajidin Muarif; Baskoro, Yogi Satriyagung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Village-level infrastructure data in Indonesia is often incomplete and outdated, making it difficult for local governments to monitor infrastructure conditions and plan development effectively. This condition was also found in Kelurahan Sisir, Kota Batu, where existing infrastructure data had not been updated and lacked integrated spatial documentation. This study aims to map the road network and public facilities in Kelurahan Sisir and to produce an accurate, up-to-date spatial database that can support the local government in development planning and decision-making. The mapping was conducted through a field survey approach integrated with Geographic Information System (GIS) technology. Initial data were collected from village documents and satellite imagery, followed by direct field surveys using smartphone-based GPS to record road networks as polylines and public facilities as points, complemented by additional attribute data and photographic documentation. The collected data were then processed using ArcGIS, incorporating administrative boundary data from Global Administrative Areas (GADM), to produce a digital infrastructure map. The results show that 17 types of infrastructure were successfully mapped, dominated by local roads (54 segments) and various public facilities, including schools, places of worship, health facilities, and government offices. The resulting map provides both theoretical contributions to the application of GIS in village-level spatial data management and practical benefits for the kelurahan, the community, and the student team involved. Field challenges such as GPS accuracy limitations, one-way road systems, and weather conditions were identified as areas for improvement in future similar activities.